Molecular mimicry in translational control of E. coli threonyl-tRNA synthetase gene. Competitive inhibition in tRNA aminoacylation and operator-repressor recognition switch using tRNA identity rules. - Romby, P (1992)
We previously showed that: (i) E.coli threonyl-tRNA synthetase (ThrRS) binds to the leader of its mRNA and represses translation by preventing ribosome binding to its loading site; (ii) the translational operator shares sequence and structure similarities with tRNA(Thr); (iii) it is possible to switch the specificity of the translational control from ThrRS to methionyl-tRNA synthetase (MetRS) by changing the CGU anticodon-like sequence to CAU, the tRNA(Met) anticodon. Here, we show that the wild type (CGU) and the mutated (CAU) operators act as competitive inhibitors of tRNA(Thr) and tRNA(fMet) for aminoacylation catalyzed by E.coli ThrRS and MetRS, respectively. The apparent Kd of the MetRS/CAU operator complex is one order magnitude higher than that of the ThrRS/CGU operator complex. Although ThrRS and MetRS shield the anticodon- and acceptor-like domains of their respective operators, the relative contribution of these two domains differs significantly. As in the threonine system, the interaction of MetRS with the CAU operator occludes ribosome binding to its loading site. The present data demonstrate that the anticodon-like sequence is one major determinant for the identity of the operator and the regulation specificity. It further shows that the tRNA-like operator obeys to tRNA identity rules.